2010
DOI: 10.1016/j.virol.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of varicella-zoster virus-encoded ORF0 gene—Comparison of parental and vaccine strains

Abstract: The varicella-zoster virus (VZV) Oka vaccine strain (vOka) differs from the parental strain (pOka) at several amino acid positions, but the mutations responsible for the attenuation of vOka have not been clearly defined. The ORF0 of vOka carries some of the mutations. Although we found that the ORF0 of both strains was incorporated into virus particles, the C-terminal region of vOka ORF0 was presented on the virion surface and was N-glycosylated, suggesting that the mutation in vOka ORF0 changes it into a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…This finding is in agreement with the results of a recent study that demonstrated that plasmid-based transient expression of P-Oka ORFS/L initiated from the 2nd predicted start codon resulted in a protein with an apparent molecular mass of approximately 17 kDa (18), which is 3 kDa larger than predicted. This report also confirmed that the discrepancy between the predicted and apparent molecular mass determined here for the P-Oka ORFS/L protein is not due to glycosylation (18). Similarly, in silico predictions indicate that ORFS/L is not myristoylated, which could also account for a deviation of the apparent from the predicted molecular mass.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is in agreement with the results of a recent study that demonstrated that plasmid-based transient expression of P-Oka ORFS/L initiated from the 2nd predicted start codon resulted in a protein with an apparent molecular mass of approximately 17 kDa (18), which is 3 kDa larger than predicted. This report also confirmed that the discrepancy between the predicted and apparent molecular mass determined here for the P-Oka ORFS/L protein is not due to glycosylation (18). Similarly, in silico predictions indicate that ORFS/L is not myristoylated, which could also account for a deviation of the apparent from the predicted molecular mass.…”
Section: Discussionsupporting
confidence: 86%
“…It was reported that the ORFS/L product was found exclusively in the cytoplasm, which is contradictory to the findings for the HSV-2 orthologue and also to the localization of the ORFS/L protein based on in silico predictions from the primary sequence (13). ORFS/L of the P-Oka strain was recently shown to be unglycosylated but present in the virion (18). Furthermore, ORFS/L expression was detected in skin lesions of individuals, as well as neurons of dorsal root ganglia, during virus reactivation (13).…”
Section: Varicella-zoster Virus ([Vzv] Human Herpesvirus 3)mentioning
confidence: 65%
“…Two putative N-linked glycosylation sites (N-X-S/T) have also been defined in the vOka ORF0 protein sequence, beginning with asparagine at residues 65 and 126 (20). The sites are present in both the wild-type and vaccine virus sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Even more surprising, we noted that VZV Ellen had exactly the same mutation in ORF0 as the vaccine strain, while lacking other shared polymorphisms with vOka (17,20). This ORF had been overlooked in the original 1986 publication of the Dumas sequence and has not been considered a prime candidate for the attenuation phenotype.…”
mentioning
confidence: 93%
“…The four coding mutations altered the amino acid sequences of ORFs 0, 1, 31, 40, and 62. A single mutation changed amino acid sequences of both ORFs 0 and 1, since these ORFs overlap in V-Oka (23). To see which of the mutated genes is responsible for the resistant phenotype, sequences of the 5 mutated ORFs were determined for three additional resistant clones, R2, R3, and R4 (Table 3).…”
Section: Identificationmentioning
confidence: 99%